SMART CITY IN SUSTAINABLE POLICY DEVELOPMENT AS A COMPETITIVENESS STRATEGY: LITERATURE REVIEW - Mardatillah, Annisa (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Smart cities in sustainable development policies are a phenomenon of rapid urbanization development and changing the urban development paradigm. This concept utilizes high technology and data analysis to improve the population's quality of life, increase the efficiency of infrastructure and services, and stimulate sustainable economic growth. Smart cities aim to create a connected and intelligent urban environment by integrating various sectors. This research uses a structured literature review method by utilizing sources such as Scopus and Google Scholar and formulates research questions related to smart cities. The questions include defining an intelligent city, benefits, implementation challenges, applications, and quantitative analysis. In addition, this research aims to analyze the implementation of smart city solutions and propose strategies to overcome emerging challenges. Data-driven solutions in smart cities can change the urban landscape by providing personalized services and addressing the need for collaboration between the private, public, and government sectors. This research indicates that using technology and innovation in policy development to create sustainable economic growth in cities involves efforts to increase the city's economy's efficiency, productivity, and competitiveness. The complexity of urban development, the application of advanced technologies, and data-driven solutions in intelligent cities promise significant progress in sustainable urban development.